Anion transport and GABA signaling - Huebner, Christian A.; Holthoff, Knut (Frontiers in Cellular Neuroscience, 2013)
Whereas activation of GABAA receptors by GABA usually results in a hyperpolarizing influx of chloride into the neuron, the reversed chloride driving force in the immature nervous system results in a depolarizing efflux of chloride. This GABAergic depolarization is deemed to be important for the maturation of the neuronal network. The concept of a developmental GABA switch has mainly been derived from in vitro experiments and reliable in vivo evidence is still missing. As GABAA receptors are permeable for both chloride and bicarbonate, the net effect of GABA also critically depends on the distribution of bicarbonate. Whereas chloride can either mediate depolarizing or hyperpolarizing currents, bicarbonate invariably mediates a depolarizing current under physiological conditions. Intracellular bicarbonate is quickly replenished by cytosolic carbonic anhydrases. Intracellular bicarbonate levels also depend on different bicarbonate transporters expressed by neurons. The expression of these proteins is not only developmentally regulated but also differs between cell types and even subcellular regions. In this review we will summarize current knowledge about the role of some of these transporters for brain development and brain function.